Transaksi Jual Beli Online Menurut Undang-Undang Perlindungan Konsumen - Nur, Andi Wahyuddin; Firsan, Muhammad; Syahbana, Muhammad Syahbana; Ramadandi; Sefiani; AU, Sitti Zulqaiddah; Masse, Nur Hayati (Legal Journal of Law, 2024)
As the use of e-commerce platforms continues to grow, consumers are increasingly exposed to a range of risks, including fraud, defective products, and a lack of transparency regarding product information. Law No. 8/1999 on Consumer Protection provides a clear legal framework to protect consumer rights. This study aims to identify potential risks, analyze the legal protection offered to consumers in online sales transactions, and make recommendations to improve the consumer protection system in Indonesia. Through a qualitative approach and secondary data analysis, this study found that despite existing regulations, there are still gaps that need to be filled in order for consumer protection to be more effective.